ESTUDO SÓCIO-AMBIENTAL DOS EFEITOS DE BARRAGENS NA ÁREA DE PROTEÇÃO AMBIENTAL DA BAIXADA MARANHENSE: O CASO DO LAGO CAJARI, PENALVA - MA. - Nascimento, Isa Rosete Mendes Araujo (2006)
During two years (2004-2006), the main effects caused by a construction of a small dam at the Cajari lake, municipality of Penalva, Baixada Maranhense region, were studied. Such construction, for being located in an ecosystem of complex structure and function and also due to the region´s dynamics of seasonal flood, a previous study on its environmental viability should have been carried out before construction, but it was not done. This study involved the lakes within Penalva municipality´s area and the Maracu channel (which links the lakes in the Penalva and Viana regions), basin of the Pindaré river. It was intended to form a base of scientifically consistent data on the environmental and socio-economic history of the dam construction in the lake Cajari. Additional objectives were to evaluate positive and negative, current and potential effects along upper and lower areas, and to discuss the cost/benefit relation of the dam construction, considering both the environment and the socio-economy of the region. Data were collected using several means: interviews, satellite imagery, tests of water quality (physical-chemical parameters and potability), flooding pulses, batimetry and hydric balance (to understand the profile of the lake´s bottom and its capacity); the data obtained were submitted to both qualitative and quantitative analyses. From the environmental standpoint, the results did not show yet clear effects from the dam on biodiversity. Regarding to the basin as a whole, it is a concern the reduction in the water flow from the Penalva region to the Viana lake. The cumulative effect of that reduction can contribute to diminish the water level in the Viana lake, and, slowly, to reduce the size of the lake itself. From a socio-economic standpoint, the effects are more positives than negatives. In general, the dam benefited fishery in the region, but caused a number of problems in the areas below it. On the other hand, the increase of fishery and the improvement in income generation are certainly desirable effects. Some sceneries area evaluated and discussed as alternatives for the sustainable use and management of water in this lacustrine region.